Porous Nanocrystalline Silicon Supported Bimetallic Pd-Au Catalysts: Preparation, Characterization, and Direct Hydrogen Peroxide Synthesis - Potemkin, Dmitriy I. (Front Chem, 2018)
Bimetallic Pd-Au catalysts were prepared on the porous nanocrystalline silicon (PSi) for the first time. The catalysts were tested in the reaction of direct hydrogen peroxide synthesis and characterized by standard structural and chemical techniques. It was shown that the Pd-Au/PSi catalyst prepared from conventional H(2)[PdCl(4)] and H[AuCl(4)] precursors contains monometallic Pd and a range of different Pd-Au alloy nanoparticles over the oxidized PSi surface. The PdAu(2)/PSi catalyst prepared from the [Pd(NH(3))(4)][AuCl(4)](2) double complex salt (DCS) single-source precursor predominantly contains bimetallic Pd-Au alloy nanoparticles. For both catalysts the surface of bimetallic nanoparticles is Pd-enriched and contains palladium in Pd(0) and Pd(2+) states. Among the catalysts studied, the PdAu(2)/PSi catalyst was the most active and selective in the direct H(2)O(2) synthesis with H(2)O(2) productivity of 0.5 [Formula: see text] at selectivity of 50% and H(2)O(2) concentration of 0.023 M in 0.03 M H(2)SO(4)-methanol solution after 5 h on stream at −10°C and atmospheric pressure. This performance is due to high activity in the H(2)O(2) synthesis reaction and low activities in the undesirable H(2)O(2) decomposition and hydrogenation reactions. Good performance of the PdAu(2)/PSi catalyst was associated with the major part of Pd in the catalyst being in the form of the bimetallic Pd-Au nanoparticles. Porous silicon was concluded to be a promising catalytic support for direct hydrogen peroxide synthesis due to its inertness with respect to undesirable side reactions, high thermal stability, and conductivity, possibility of safe operation at high temperatures and pressures and a well-established manufacturing process.